The magic order. Vol. 1 - Millar, Mark (Image Comics, 2020)
"We live in a world where we've never seen a monster, and The Magic Order is the reason we sleep safely in our beds. Magic meets the Mob in The Magic Order, as five families of magicians -- sworn to protect our world for generations -- must battle an enemy who's picking them off one by one. By day, they live among us as our neighbors, friends and co-workers, but by night they are the sorcerers, magicians and wizards that protect us from the forces of darkness ... unless the darkness gets them first."--Provided by publisher.